2011
DOI: 10.1007/s10157-011-0421-5
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin induces Sirt1 in association with histone deacetylation and increased Werner syndrome protein in the kidney

Abstract: These findings collectively suggest that CDDP increases the level of Sirt1 protein in the kidneys in association with histone H3 deacetylation and increased WRN and PCNA production. The induced Sirt1 may work defensively to mitigate CDDP-induced tubular damage by inactivating core histone transcriptionally, and by repairing DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…As a transcriptional repressor, Hdac5 has been implicated in disease conditions including AKI. Induction of Hdac5 has been reported in cisplatin-induced AKI 63 and septic AKI 64 , which is associated with BMP7 suppression, leading to the inhibition of tubular cell proliferation and repair. Future investigation should extend to these genes to have a comprehensive understanding of DNA methylation in AKI.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcriptional repressor, Hdac5 has been implicated in disease conditions including AKI. Induction of Hdac5 has been reported in cisplatin-induced AKI 63 and septic AKI 64 , which is associated with BMP7 suppression, leading to the inhibition of tubular cell proliferation and repair. Future investigation should extend to these genes to have a comprehensive understanding of DNA methylation in AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that SIRT1 is an important nicotinamide adenine dinucleotide (NAD + )-dependent deacetylase which regulates stress responses, inflammation, apoptosis and cellular senescence, and plays an important role in the development of several renal diseases474849505152, we investigated its expression in rat renal tissue after severe burns. It was showed that the level of SIRT1 was decreased after burns and recovered after the administration of melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 plays an important role in the development of several renal diseases474849505152, and its activation reduces the occurrence of AKI induced by drugs, toxicants and ischemic-reperfusion injury. In mouse proximal tubular epithelial cell model, the administration of cis-platinum leads to the inhibition of SIRT1 as well as ac-p53, PUMA-α, Bax and cleaved-caspase-3, while resveratrol can reverse the effects47.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular evidence has indicated that expression of SIRT1 is able to decrease the acetylation of NF-κB and reduce the toxic effect of cisplatin on kidney tubules. Additionally, a previous study indicated that abnormal activation of NF-κB may promote inflammatory responses and autoimmune responses, which results in the expansion of the extracellular matrix, inflammatory cell infiltration and renal tubule interstitial fibrosis (33).…”
Section: Discussionmentioning
confidence: 99%